(untitled) (Research, Society and Development, 2021)
Objective: to identify the evidence available in the literature about the changes that occurred in the lives of people after bariatric surgery. Methods: integrative literature review, with a search for studies published between January 2016 and February 2020, carried out in the following databases: Cochrane Library, Embase (Elsevier), US National Library of Medicine (Pubmed) and Virtual Health Library (VHL) in April 2020. Searches were obtained by crossing, in the databases, the following descriptors: Obesity, Bariatric Surgery, Quality of life. For the organization of the results, the flowchart recommended by PRISMA was used. For the operationalization of the results, the Iramuteq® software was adopted. Results: 14 articles comprised this review, which presented the main changes after performing bariatric surgery. The findings were divided into three classes: Physical changes after bariatric surgery; Improvement in quality of life after bariatric surgery; and Stigma associated with the surgical procedure as a strategy for weight loss. Conclusion: it was identified that the changes in people’s lives after bariatric surgery pervade physical, psycho-emotional and interpersonal relationships.